Understanding livelihood strategies of urban women traders : a case of Magaba, Harare in Zimbabwe - Chirau, Takunda John (Rhodes University, Faculty of Humanities, Department of Sociology, 2013)
This thesis seeks to understand and analyze the livelihood strategies of urban women traders at Magaba in Harare (Zimbabwe) in the context of the contemporary economic and political crisis. The crisis emerged in the 1990s with the introduction of a structural adjustment programme and deepened further with the fast track land reform programme initiated by the Zimbabwean government in the year 2000. The crisis has involved a down-sizing of the Zimbabwean economy and a massive rise in the rate of unemployment in the formal economy. Consequently urban life became increasingly unbearable for poor blacks and informal economic activities blossomed and started to make a significant contribution to household income and livelihoods. The role of women in the informal economy was particularly pronounced. Theoretically, the thesis is underpinned by the sustainable livelihoods framework. In examining the vulnerability context of the Magaba women traders and the institutional interventions which complicate the lives and livelihoods of these traders, I identify and unpack their diverse livelihood activities and strategies and the resources (or assets) they deploy in constructing urban livelihoods. Though their livelihood portfolios complement any earnings from formal employment by household members and though they contribute to their household's sustenance, there are a number of daily challenges which they face in their trading activities and which they seek to counteract through a range of often ingenious coping mechanisms. The thesis is important for a number of reasons. It fills an important empirical gap in the study of Magaba market specifically, it brings to the fore the gendered character of the informal trading activities in urban Zimbabwe, and it deploys the livelihoods framework in a manner which is sensitive to both structure and agency.
Keywords: Street vendors -- Zimbabwe -- Harare; Women -- Zimbabwe -- Harare -- Social conditions; Women -- Zimbabwe -- Harare -- Economic conditions; Urban poor -- Zimbabwe -- Harare